Analisis Pengaruh Strategi Promosi, Citra Merek Dan Persepsi Terhadap Keputusan Nasabah Pengguna Tabungan Emas Pada PT.Pegadaian (Persero) Cabang Jombang - Mutiara Pertiwi; Intan Mazidah Permatasari; Syahrial Umardany; Chamariyah Chamariyah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
The increasingly growing world economic developments of companies are competing to show each other the quality of their goods with other companies, and many consumers are beginning to invest in what areas are benefiting. Gold investment is a simple investment form. Because this investment can be done by anyone, whether they are from the educated or not, by investing gold in the form of gold coins and gold bullion. This study aims to determine simultaneously and partially promotional strategies, brand image and perceptions of users of gold savings at PT. Pegadaian (Persero) JOMBANG. The type of research used is associative. The population in this study 88.10 with a sample of 88 respondents. Data analysis techniques use multiple linear regression. The results showed simultaneously and partially promotion strategy, brand image and perception have a significant effect on purchasing decision. In the application of its marketing strategy should pay more attention to the brand image, given the image of gold jewelry brand on the consumer has not been embedded properly. This can be done for example by improving marketing and marketing communications programs to educate consumers about benefits and branding, through appropriate advertising strategies.